Caleidoscópio Byung-Chul Han : versão integral v.6, n.1. - Editorial, (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
Versão integral do v.6, n.1: Caleidoscópio Byung-Chul Han